2016
DOI: 10.1177/0265407515597562
|View full text |Cite
|
Sign up to set email alerts
|

The calm after the storm

Abstract: We examined whether seven relational constructs (satisfaction, commitment, closeness, conflict, ambivalence, maintenance, and love) showed significant within-person residual variance over time (variability), whether couple members were similar in their variability (covariation), and whether variability and covariation differed by relationship length. We used dyadic daily diary data from 157 couples together from 2 months to 44 years. Each relational construct significantly varied within person from day to day,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Longitudinal research has also demonstrated links between commitment and later stability (Rhoades, Stanley, & Markman, 2010). Further, daily diary studies have found that commitment demonstrates statistically significant within-person variability across 7 days and is therefore appropriate for examination on a day-to-day basis (Totenhagen, Butler, Curran, & Serido, 2016). Because our data include reports over a 14-day period, which is consistent with our daily diary design, we assessed commitment as a form of relational stability.…”
Section: Stressful Events and Relationship Functioningmentioning
confidence: 81%
See 3 more Smart Citations
“…Longitudinal research has also demonstrated links between commitment and later stability (Rhoades, Stanley, & Markman, 2010). Further, daily diary studies have found that commitment demonstrates statistically significant within-person variability across 7 days and is therefore appropriate for examination on a day-to-day basis (Totenhagen, Butler, Curran, & Serido, 2016). Because our data include reports over a 14-day period, which is consistent with our daily diary design, we assessed commitment as a form of relational stability.…”
Section: Stressful Events and Relationship Functioningmentioning
confidence: 81%
“…First, given the range of relationship length for couples in the present study (i.e., less than 1 year to 35 years) and the possibility that individual variability and couple covariability may differ in relational constructs in newer versus longer-term relationships (Totenhagen et al, 2016), we computed relationship length in months and centered it around the grand mean to use it as a control variable. First, given the range of relationship length for couples in the present study (i.e., less than 1 year to 35 years) and the possibility that individual variability and couple covariability may differ in relational constructs in newer versus longer-term relationships (Totenhagen et al, 2016), we computed relationship length in months and centered it around the grand mean to use it as a control variable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the extent that constructs of interest are significantly associated with this remaining within-person residual variance, these constructs are thus predicting volatility in perceived relationship quality. In SAS PROC MIXED, the repeated statement is what is used to permit the inclusion of between-person predictors of within-person residual variance (see Hoffman, 2007;Totenhagen et al, 2016).…”
Section: Resultsmentioning
confidence: 99%